2016
DOI: 10.1101/090027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge-guided gene prioritization reveals new insights into the mechanisms of chemoresistance

Abstract: Background: Identification of genes whose basal mRNA expression predicts the sensitivity of

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 82 publications
(97 reference statements)
0
20
0
Order By: Relevance
“…To develop a gene signature corresponding to reactive stroma in the FinHer HER2‐positive cohort (HER2STROMA—Supporting Information Table S1), we used a method called ProGENI, implemented as part of the KnowEnG analytical platform (http://www.knoweng.org). ProGENI is a gene prioritization method that combines information on “omics” profiles of samples with a network of gene–gene interactions to improve the accuracy of prioritization.…”
Section: Methodsmentioning
confidence: 99%
“…To develop a gene signature corresponding to reactive stroma in the FinHer HER2‐positive cohort (HER2STROMA—Supporting Information Table S1), we used a method called ProGENI, implemented as part of the KnowEnG analytical platform (http://www.knoweng.org). ProGENI is a gene prioritization method that combines information on “omics” profiles of samples with a network of gene–gene interactions to improve the accuracy of prioritization.…”
Section: Methodsmentioning
confidence: 99%
“…We made available as an online resource all (TF, Drug) associations validated using siRNA or overexpression experiments in this study as well as those found to be similarly validated in our survey of the literature (Supplemental Note S1-S2), the GENMi study (Hanson et al 2015), and a related work that performs the same experimental validations (Emad et al 2017). This resource is available at veda.…”
Section: Database Of (Tf Drug) Associationsmentioning
confidence: 89%
“…On a relatively minor note, the above methods for reconstructing context-specific transcriptional regulatory networks require data on discrete cellular conditions (disease versus nondisease state, for instance) and are thus distinct from pGENMi, which focuses on interindividual continuous variation in cellular phenotype. TF associations with drugs can also be inferred from general studies that prioritize genes related to drug response based on prior functional networks (Morrison et al 2005;Chen et al 2012;Emad et al 2017) or based on observed or imputed gene expression alone (Barretina et al 2012;Basu et al 2013;Gusev et al 2016;Rees et al 2016). These approaches are not focused on identifying regulators of phenotype based on cis-regulatory evidence.…”
Section: Discussionmentioning
confidence: 99%
“…This process was repeated 200 times, each time using a distinct random partition of data. The Cox regression model using EMAT labels along with clinical parameters provided the best predictions (Figure 2A-C bottom panels), evaluated using a one-sided Wilcoxon signed rank test on paired C-index values of the compared methods as well as another measure called percentage of improved folds (PIF) (Emad, Cairns et al, 2017) defined as percent of the partitions in which one class of features outperforms another class.…”
Section: Figurementioning
confidence: 99%